Trends in police-recorded offenses at the beginning of the twenty-first century in Europe - Gruszczyńska, Beata (European journal on criminal policy and research, 2018)
This study explores the trends in police-recorded crimes in Europe and in individual countries. The offender characteristics such as gender and age of perpetrators are also considered. In addition, the analysis discusses factors behind the changes in the crime trends. Data were collected for the European Sourcebook of Crime and Criminal Justice Statistics by means of an electronic questionnaire, with the help of national correspondents. The dataset comprises metadata and crime rates (crimes/100,000 population) for 21 offense types. This article focuses on the results from the years 2000–2011. The overview of European crime trends is based on an analysis of the average annual change in homicide, assault, rape, burglary, car theft, robbery, and drug offenses. The trends in different crime categories vary: homicide has decreased in all European countries, and the decrease has been more rapid in those countries with a high homicide rate. However, the development of all violent crime seems contradictory, because assault and rape rates have increased in many countries. Property crimes, such as robbery, burglary and car theft, have decreased, but drug crimes show an increase. Overall, the findings suggest that property is currently better secured now than at the beginning of the century, but the situation in respect of violent crimes (excluding homicide) and drug crimes has not improved. In the future, efforts should be made to collect Europe-wide victimization survey data to supplement and deepen the understanding of the development of crime. In spite of the limitations, for the moment police trends are especially important, because up-to-date European victimization survey figures are not available.